Relationships of the gut microbiome with cognitive development among healthy school-age children - Lapidot, Yelena; Maya, Maayan; Reshef, Leah; Cohen, Dani; Ornoy, Asher; Gophna, Uri; Muhsen, Khitam (Frontiers in Pediatrics, 2023)
Background The gut microbiome might play a role in neurodevelopment, however, evidence remains elusive. We aimed to examine the relationship between the intestinal microbiome and cognitive development of school-age children. Methods This cross-sectional study included healthy Israeli Arab children from different socioeconomic status (SES). The microbiome was characterized in fecal samples by implementing 16S rRNA gene sequencing. Cognitive function was measured using Stanford-Binet test, yielding full-scale Intelligence Quotient (FSIQ) score. Sociodemographics and anthropometric and hemoglobin measurements were obtained. Multivariate models were implemented to assess adjusted associations between the gut microbiome and FSIQ score, while controlling for age, sex, SES, physical growth, and hemoglobin levels. Results Overall, 165 children (41.2% females) aged 6–9 years were enrolled. SES score was strongly related to both FSIQ score and the gut microbiome. Measures of α-diversity were significantly associated with FSIQ score, demonstrating a more diverse, even, and rich microbiome with increased FSIQ score. Significant differences in fecal bacterial composition were found; FSIQ score explained the highest variance in bacterial β-diversity, followed by SES score. Several taxonomic differences were significantly associated with FSIQ score, including Prevotella, Dialister, Sutterella, Ruminococcus callidus, and Bacteroides uniformis. Conclusions We demonstrated significant independent associations between the gut microbiome and cognitive development in school-age children.